Inventory of Yard Plant Species in Mulyasri Village, Tomoni District, East Luwu As a Source of Learning Biology - Ersa Rana; Hamka Lodang; Muh. Wiharto (Indonesian Journal of Biology Education, 2023)
This research was conducted in Mulyasri Village, Tomoni District, East Luwu Regency. The purpose of this study was to determine the types of yard plants that were deliberately planted in the yards of residents of Mulyasri Village, Tomoni District, East Luwu Regency; and to find out the output of plant inventory results that are used as a source of learning biology. This research method is a descriptive method and an exploration method. The results showed that there were 77 species of yard plants that were found and identified to the species level and classified into the kingdom plantae. There are two groups of plants found, namely spike plants (Pteridophyta) and flowering plants (Magnoliphyta). Spike plants (Pteridophyta) are found in 2 families with 2 species. Flowering plants (Magnoliphyta) are found in 38 families with 75 species. The results of the identification of the yard plants were compiled into a learning resource in the form of Flora which contains plant images, classifications, descriptions, local names and benefits of yard plant species found to be recommended as learning resources that students can use to increase knowledge about biological materials.